2010
DOI: 10.1007/s10620-009-1092-x
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Undergo Split-Dose Bowel Preparation for Colonoscopy and Compliance with Split-Dose Instructions

Abstract: Acceptance of and compliance with split-dose bowel preparations is high and should not be a deterrent to prescribing split-dose preparations for colonoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 22 publications
3
30
0
2
Order By: Relevance
“…It was a retrospective review of colonoscopies, andthe fact that bowel preparations were selected at the discretion of the endoscopists, resulted in uneven sample sizes among the different groups. The lack of patient satisfaction data limits our ability to assess compliance, which may have contributed to the effectiveness of each of the bowel preparations [10,17,[35][36][37] . Nevertheless, this real-world experience of bowel preps for colonoscopy in nearly 3,600 patients confirms that split dosing is superior to prior day dosing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was a retrospective review of colonoscopies, andthe fact that bowel preparations were selected at the discretion of the endoscopists, resulted in uneven sample sizes among the different groups. The lack of patient satisfaction data limits our ability to assess compliance, which may have contributed to the effectiveness of each of the bowel preparations [10,17,[35][36][37] . Nevertheless, this real-world experience of bowel preps for colonoscopy in nearly 3,600 patients confirms that split dosing is superior to prior day dosing.…”
Section: Discussionmentioning
confidence: 99%
“…compliance have also been shown to be superior with SD compared to DPD preparations [10,17,18] . The aim of this study was to evaluate the effectiveness of the four most commonly used bowel preparations in our tertiary center endoscopy unit to determine whether any differences exist between the preps and whether there was a correlation between split dosing or day-prior dosing and the effectiveness of the bowel preparation in a non-study setting.…”
Section: Timing Of Colonoscopymentioning
confidence: 99%
“…Physicians often assume that their patients would not be willing to follow a recommendation of split doses [59] . Nevertheless, in a survey study in the US, when patients were explained the importance of the same-day schedule, over 85% were willing to wake up during the night to drink the second dose of a split preparation, and 78% of those who had early morning appointments actually did so [60] . There is abundant evidence indicating that bowel preparation should be administered at least in part on the same day as the examination, in relation to effectiveness of bowel cleansing and detection of neoplasms.…”
Section: A Key Factor For Optimal Preparation: Timing Of Administrationmentioning
confidence: 99%
“…Recent studies have shown that split-dosing of the bowel preparation improves the quality of colon cleansing and may also improve tolerability [2,3,4,5,6]. In the current clinical practice, split-dosing of 4 liters of PEG is adopted as a standard regimen for bowel preparation.…”
Section: Introductionmentioning
confidence: 99%